Amplification of Artificial Intelligence in 2024 Election News in Online Media in Indonesia - Stefanny Tirza Kurniawan (Journal of Politica Governo, 2024)
This research discusses framing carried out by online media, Detik.com, which conveys the potential use of artificial intelligence (AI) and its impact in elections. The massive involvement of artificial intelligence (AI) in people's daily lives opens up great opportunities for the involvement of artificial intelligence (AI) as an efficient and effective campaign suggestion. This research aims to investigate the framing carried out by Detik.com in an article entitled "IPB Experts Predict AI Will Affect the 2024 Election, Like What?", published in Detik.com on Wednesday, September 13, 2023. This study uses the Fairhurst and Sarr framing method. This study found that media framing tends to support the use of AI in elections, especially in campaigns.